1996
DOI: 10.1177/00220345960750110601
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acetone, Ethanol, HEMA, and Air on the Stiffness of Human Decalcified Dentin Matrix

Abstract: During resin-bonding procedures, dentin surfaces are treated with acidic conditioners to remove the smear layer and decalcify the surface to expose the collagen fibrils of the underlying matrix. These decalcified surfaces are then either air-dried or treated with dehydrating solvents, procedures which may modify the physical properties of the dentin matrix. The purpose of this study was to evaluate the effects of dehydration on the stiffness of the decalcified dentin matrix. Small (8 x 1.7 x 0.9 mm) beams of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
129
2
22

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 20 publications
6
129
2
22
Order By: Relevance
“…[11][12] Slow water absorption by bonded constituents can lead to the degradation of bond strengths, because of hydrolysis of the adhesive resin [13][14] and possibly the plasticizing effects of water on resin and collagen. 12 Thermocycling is the in vitro process of subjecting a restoration and tooth to temperature limits similar to those experienced in the oral cavity, which can produce potential negative effects due to dissimilar coefficients of thermal expansion between the tooth and the restorative material. 15 Thermocyling stresses the bond between resin and the tooth, and it may affect bond strength, depending on the adhesive system.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] Slow water absorption by bonded constituents can lead to the degradation of bond strengths, because of hydrolysis of the adhesive resin [13][14] and possibly the plasticizing effects of water on resin and collagen. 12 Thermocycling is the in vitro process of subjecting a restoration and tooth to temperature limits similar to those experienced in the oral cavity, which can produce potential negative effects due to dissimilar coefficients of thermal expansion between the tooth and the restorative material. 15 Thermocyling stresses the bond between resin and the tooth, and it may affect bond strength, depending on the adhesive system.…”
Section: Introductionmentioning
confidence: 99%
“…The collagen fibrils form weak interpeptide bonds that render the matrix shrunk, stiff [19][20] and practically impermeable to resin adhesives, reducing the infiltration rate of the bonding resin within the hybrid layer to approximately 50% when applied to dry instead of wet dentin. [3][4]21 Previous studies have reported that the adverse effect of over-drying could be reversed by vigorously rubbing the adhesive on the dentin substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Этанол, как и вода, полярный протонный растворитель, но из-за своей низкой диэлектрической константы он более подходит к менее полярным растворенным веществам [4,23,24]. Этанол образует водородные связи с водой и улучшает ее испарение с поверхности зуба, именно поэтому спирт и вода используются как ко-растворители.…”
unclassified
“…Этанол образует водородные связи с водой и улучшает ее испарение с поверхности зуба, именно поэтому спирт и вода используются как ко-растворители. Maciel et al обнаружили, что этанол также укрепляет волокна коллагена, тем самым уменьшая их коллапсирование при испарении растворителя [23][24][25]. Ацетон -растворитель с высоким дипольным моментом и низкой диэлектрической константой [4,23,25].…”
unclassified
See 1 more Smart Citation